Long hospitalization for severe ovarian hyperstimulation syndrome with persistent right hydrothorax and two occurrences of pneumonia. Issue 3 (11th January 2017) - Lin, Jinli; Li, Xueying; Zhang, Linhao
Abstract : During prolonged hospitalization for ovarian hyperstimulation syndrome, a patient experienced persistent right hydrothorax and repeated pneumonia. More aggressive treatment should be considered for such patients.